Analysis of sea almond (Terminalia catappa) cracking sites used by wild Burmese long‐tailed macaques (Macaca fascicularis aurea). Issue 5 (5th January 2017) - Falótico, Tiago; Spagnoletti, Noemi; Haslam, Michael; Luncz, Lydia V.; Malaivijitnond, Suchinda; Gumert, Michael
Abstract : Nut‐cracking is shared by all non‐human primate taxa that are known to habitually use percussive stone tools in the wild: robust capuchins ( Sapajus spp.), western chimpanzees ( Pan troglodytes verus ), and Burmese long‐tailed macaques ( Macaca fascicularis aurea ). Despite opportunistically processing nuts, Burmese long‐tailed macaques predominantly use stone tools to process mollusks in coastal environments. Here, we present the first comprehensive survey of sea almond ( Terminalia catappa ) nut‐cracking sites created by macaques. We mapped T. catappa trees and nut‐cracking sites that we encountered along the intertidal zone and forest border on the coasts of Piak Nam Yai Island, Thailand. For each nut‐cracking site, we measured the physical properties (i.e., size, weight, use‐wear) of hammer stones and anvils. We found that T. catappa trees and nut‐cracking sites primarily occurred on the western coast facing the open sea, and cracking sites clusters around the trees. We confirmed previous results that nut cracking tools are among the heaviest tools used by long‐tailed macaques; however, we found our sample of T. catappa stone tools lighter than a previously collected sea almond sample that, unlike our sample, was collected immediately after use within the intertidal zone. The difference was likely the result of tidal influences on tool‐use sites. We also found that tool accumulations above the intertidal region do not resemble those within them, possibly leading to incomplete assessments of macaque stone tools through archaeological techniques that would use these durable sites. Abstract : Long‐tailed macaques create clusters of sea almond cracking sites around the trees, using stone tools that are among the heaviest used by the macaques. The tool accumulations in the intertidal region appears to be affect by tides.